THE INFLUENCE OF INDIVIDUAL ABILITIES AND INDIVIDUAL CHARACTERISTICS ON THE SERVICE QUALITY OF SERBA JADI DISTRICT OFFICE EMPLOYEES - Indra Welly Arifin; Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk; Nikson Sitindaon (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research aims to determine the influence of individual abilities and individual characteristics on the service quality of employees at the Multipurpose District Office in Serdang Bedagai Regency. The type of research used is quantitative research. The nature of this research is replication. The analytical method used is a multiple linear regression model to determine the direction of the relationship between the independent and dependent variables, whether each variable has a positive or negative relationship. The results of this research testing the first hypothesis are accepted, meaningvariableIndividual Abilitiesinfluentialon the Multipurpose District Office Service Quality variable. The second hypothesis test is accepted, meaningvariableIndividual Characteristicsinfluentialon the Multipurpose District Office Service Quality variable. The third hypothesis test is accepted, meaning the Individual Ability variable and the Individual Characteristics variablehave a joint (simultaneous) effect onService qualityMultipurpose District Office. It is better to hope that the Serdang Bedagai District Office of Serdang Bedagai Regency can better appreciate or appreciate every work that has been completed by its employees, which can be shown by expressions given directly or by rewards for employees in order to improve employee performance.